Seismic behavior of composite shear walls incorporating high-strength materials and CFST boundary elements. (1st October 2020) - Zhang, Jianwei; Li, Xiangyu; Cao, Wanlin; Yu, Cheng
Highlights: The cyclic behavior of the proposed composite shear walls was investigated. The use of SRUHS bars was beneficial to improve the reparability of the walls. Steel fibers could improve the deformation capacity of the composite walls. A damage index was calculated in terms of hysteresis characteristics. A prediction model for the lateral bearing capacity was proposed and verified. Abstract: An innovative shear wall was proposed, which was composed of high-strength concrete and steel rebars, as well as concrete-encased CFST columns embedded at boundary elements. To study the cyclic and resilient behavior of the proposed wall, four walls with shear span ratios of 2.2 were designed and tested under quasi-static cyclic loads. The test parameters were the type of longitudinal bars at boundary elements, the presence of steel fibers, and the axial compression ratio. As test results showed, within the limit of axial compression ratio, the proposed shear walls had small residual deformation until a 2% loading drift ratio; after that, the hysteresis curve became full and the energy dissipation capacity increased, indicating the desirable collapse resistance. Specifically, the use of ultra-high strength longitudinal bars at boundary elements significantly decreased the residual deformation and improved the reparability. In addition, steel fibers effectively enhanced the deformation capacity of the proposed walls. Finally, given the confined effects of CFST columns and stirrups on concrete, a prediction model for the lateral load-bearing capacity was established. The comparison between predicted and test results from this study and existing research verified the good accuracy of this model.